2021
DOI: 10.37819/biosis.002.01.0095
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic Lexicon: The Onshore Cenozoic Sedimentary Formations of The Republic of Panama

Abstract: The stratigraphic knowledge of Panama was, until now, spread over hundreds of scientific/geologic publications written during the past 120 years. The construction of the Panama Canal during the early twentieth century helped galvanizing the engineering and geological disciplines to understand the tectonic, sedimentation and biodiversity of the Cenozoic Era in this part of the world. Later, few petroleum companies arrived on the scene and contributed to our knowledge of the sub-surface. The past thirty years sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 106 publications
(617 reference statements)
0
3
0
Order By: Relevance
“…The marine rocks of the Culebra Formation are lower Miocene (uppermost Aquitanian-lower Burdigalian), and not Oligocene as assumed by Rathbun, 1918Rathbun, [1919 and repeated as such by subsequent authors (see notes in Luque et al, 2017). At its base, the marine Culebra Formation overlies in sharp unconformity the terrestrial upper Oligocene-lower Miocene rocks of the Las Cascadas Formation, and its top, it underlies conformably the coarser terrestrial rocks of the upper Lower to Middle Miocene Cucaracha Formation (Montes et al, 2012;Buchs et al, 2019;LeBlanc, 2021). Kirby et al (2008) reported Sr isotope dating ages for different parts of the formation, including four ages from Acropora corals and pectinids in the middle member of the Culebra Formation (Emperador Limestone), ranging between 21.24±0.44 and 20.62±0.58 Ma, and two ages of from a pectinid and an ostreid (19.83±0.39 and 19.12±0.42 Ma, respectively), from the lowermost portion of the Cucaracha Formation, above the top of the upper member of the Culebra Formation (Kirby et al, 2008, fig.…”
Section: Age Justificationmentioning
confidence: 85%
“…The marine rocks of the Culebra Formation are lower Miocene (uppermost Aquitanian-lower Burdigalian), and not Oligocene as assumed by Rathbun, 1918Rathbun, [1919 and repeated as such by subsequent authors (see notes in Luque et al, 2017). At its base, the marine Culebra Formation overlies in sharp unconformity the terrestrial upper Oligocene-lower Miocene rocks of the Las Cascadas Formation, and its top, it underlies conformably the coarser terrestrial rocks of the upper Lower to Middle Miocene Cucaracha Formation (Montes et al, 2012;Buchs et al, 2019;LeBlanc, 2021). Kirby et al (2008) reported Sr isotope dating ages for different parts of the formation, including four ages from Acropora corals and pectinids in the middle member of the Culebra Formation (Emperador Limestone), ranging between 21.24±0.44 and 20.62±0.58 Ma, and two ages of from a pectinid and an ostreid (19.83±0.39 and 19.12±0.42 Ma, respectively), from the lowermost portion of the Cucaracha Formation, above the top of the upper member of the Culebra Formation (Kirby et al, 2008, fig.…”
Section: Age Justificationmentioning
confidence: 85%
“…Other than the expected detailed discussion on the stratigraphy of the four formations and their members, this highly illustrated revision introduces the following topics: ORIGINAL RESEARCH LeBlanc (2021) Biosis: Biological Systems (2021) 2(4) 2 Umm Bab dolomite and Limestone Member; LeBlanc (2019). f. Discusses the paleo-fluid escape structures associated with the occurrence of silica in younger layers; LeBlanc (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Biosis: Biological Systems ( 2021) 2( 4) LeBlanc (2021) 3 Note 1: Color codes and Stage names are taken from the "Commission for the Geological Map of the World (CGMW)", Paris, France. Note 2: The "Rujm Aïd Velates limestone Member" of Cavelier (1975), also previously known as "Fhaihil Velates Limestone Member" of Cavelier, (1970a), formerly at the base of the Dammam Formation is now obsolete.…”
Section: Introductionmentioning
confidence: 99%